Desenvolvimento e validação de sistemas de monitoramento de baixo custo de temperatura e umidade relativa do ar - Rêgo, Márlison de Sá (2016)
From the perspective of optimizing the planning, management and management of water resources in the national context the hydrometeorological monitoring systems have gone through the process of technological innovation. Increased monitoring of potential for reduced costs and improved quality of monitored data motivate this field of research. Starting from the importance of the variables of temperature and relative humidity among the variables monitored, this paper proposes the development of three hardware systems and software based on an open platform, which measure these values accurately from three sensors low cost, RHT01, RHT02 and RHT03 available in the market from the year 2005. These sensors are part of the advancement of sensor lines, newly created, polymer and semiconductor oxides. The technological base of each system is the microcontroller "arduino rev. 3 ", which he managed an electronic circuit capable of collecting and storing data from hydro-meteorological variables, in a flash memory device (sd card). Then, in order to check the reliability on the operation, each system was subjected to three data collection tests, at three different sites operating simultaneously with conventional systems used by the Micrometeorology Laboratory of UFSM (LMMET/UFSM). Local tests are situated in the municipality of Santa Maria, in the state of Rio Grande do Sul, Brazil. The microclimate conditions were different among trials due to location. The first test was performed on the terrace of the INPE-UFSM facilities, the second test in micrometeorology Laboratory of UFSM and the third in a rural area of central campus of UFSM, characterized by the pampa biome, which is located a network monitoring tower micro-sulfux. The collections occurred during the months from April to June, representing the final step of the fall season and the beginning of winter in 2015. The first trial lasted eleven days, the second and third Thirteen Eleven. The time discretization of the collections was a minute. With the data collected was carried out comparative analysis of inexpensive and conventional systems by graphic systems for analysis, descriptive statistics, and statistics such as Pearson correlation coefficients, ANOVA and Tukey test. With determination coefficient values (R2) higher than 0.90 in all tests and no significant difference between low-cost sensors and analyzed conventional systems, with only one exception, the results indicated the feasibility of using these sensors to generate Data medium temperature and relative humidity for a minimum time interval from generation 1 minute, 15 minutes, 30 minutes and 1 hour. The results also indicated the possibility of further quantitative research on the influence of the sensors under the measured data.